Effectiveness of Black Soldier Fly Larvae (Hermetia Illucens) as a Decomposer of Organic Waste in Food Court Sabilurrasyad Gorontalo State University - Putri Adelina Mokodenseho; Herlina Jusuf; Tri Septian Maksum (Universitas Muhammadiyah Palu, 2025)
Organic waste that is not managed quickly will create bad odors and cause disease. One way to reduce the weight of organic waste is to use black soldier fly larvae. The purpose of the study was to determine the effectiveness of black soldier fly larvae (Hermetia illucens) as a decomposer of organic waste at the Sabilurrasyad Food Court, Gorontalo State University. The type of research used is pre-experiment with a One-Shot Case Study design. The samples were vegetable organic waste, chicken waste and fish residue weighing 2500 grams each, as well as 250 grams of black soldier fly larval samples for each type of feed obtained using the purposive sampling technique. Data analysis used the Kruskal Wallis test with = 5% (0.05). The results showed that the larval growth rate of vegetable type was 10.58 grams, chicken residue -4 grams, leftover fish -4.3 grams and substrate consumption ability of vegetable type 66.60%, chicken residue 9.48%, fish residue 16.64% with the same data analysis results, namely p-value = 0.368 > 0.05. In conclusion, there was no significant difference in larval growth rate and substrate consumption ability for the type of vegetable waste, chicken leftovers and fish leftovers. It is recommended to carry out variations and combinations of feed as well as temperature and humidity measurements for more optimal growth of black soldier fly larvae and more effectively decomposing organic waste.